Influência do uso de combustíveis alternativos na síntese por combustão via microondas para a produção de materiais cerâmicos com estrutura espinélio - Silva, Walquiria Joseane da (2011)
The development and study of detectors sensitive to flammable combustible and toxic gases at low cost is a crucial technology challenge to enable marketable versions to the market in general. Solid state sensors are attractive for commercial purposes by the strength and lifetime, because it isn t consumed in the reaction with the gas. In parallel, the use of synthesis techniques more viable for the applicability on an industrial scale are more attractive to produce commercial products. In this context ceramics with spinel structure were obtained by microwave-assisted combustion for application to flammable fuel gas detectors. Additionally, alternatives organic-reducers were employed to study the influence of those in the synthesis process and the differences in performance and properties of the powders obtained. The organic- reducers were characterized by Thermogravimetry (TG) and Derivative Thermogravimetry (DTG). After synthesis, the samples were heat treated and characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), analysis by specific area by BET Method and Scanning Electron Microscopy (SEM). Quantification of phases and structural parameters were carried through Rietveld method. The methodology was effective to obtain Ni-Mn mixed oxides. The fuels influenced in obtaining spinel phase and morphology of the samples, however samples calcined at 950 °C there is just the spinel phase in the material regardless of the organic-reducer. Therefore, differences in performance are expected in technological applications when sample equal in phase but with different morphologies are tested